COMPUTATIONAL FLUID DYNAMICS (CFD) SIMULATION OF BYPASS FRACTION FOR BYPASS PIG IN MULTIPHASE FLOW - MUHAMMAD NUR AZLEE STANLEY, MUHAMMAD NUR AFIF DANIAL (IRC, 2020)
The horizontal pipeline is a common piping system in the oil and gas industries that has been used to distribute two-phase flow. However, slug flow is one of the major problems in the two-phase flow. The slug generation occurs because of the increase in gas velocity that allows the liquid surface to move upward to the top of the pipe and to form an elongated bubble. It is important to understand the slug flow characteristics which could affect the pipeline system.